2022
DOI: 10.1186/s12913-022-07665-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patient safety culture in 15 intensive care units: a mixed-methods study

Abstract: Background Within hospitals, intensive care units (ICUs) are particularly high-risk areas for medical errors and adverse events that could occur due to the complexity of care and the patients’ fragile medical conditions. Assessing patient safety culture (PSC) is essential to have a broad view on patient safety issues, to orientate future improvement actions and optimize quality of care and patient safety outcomes. This study aimed at assessing PSC in 15 Tunisian ICUs using mixed methods approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…In our study, the dimension “Frequency of events reported” (D2) initially had a score of 30.1% and was therefore a dimension to be improved. This score was close to those reported by two other Tunisian studies conducted in intensive care units (ICUs) [ 2 ] and in operating rooms [ 18 ] and which respectively found scores of 20.8% and 25.6%. Also, a study carried out in a maternity hospital in Switzerland in 2022 showed that this dimension was among the least developed ones with a score of 20.8% [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, the dimension “Frequency of events reported” (D2) initially had a score of 30.1% and was therefore a dimension to be improved. This score was close to those reported by two other Tunisian studies conducted in intensive care units (ICUs) [ 2 ] and in operating rooms [ 18 ] and which respectively found scores of 20.8% and 25.6%. Also, a study carried out in a maternity hospital in Switzerland in 2022 showed that this dimension was among the least developed ones with a score of 20.8% [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…The dimension "Non-punitive response to error" (D7) may confirm this where, before the intervention, it had a score of 21.1%, meaning that the majority of staff feel that mistakes are blamed on them and that when an event is reported, it is the person who is singled out and not the problem. Others point out that the existing reporting system lacks responsiveness and does not go further than reporting, which explains the low rate of AEs reporting [2,18]. This low tendency to report and this limited reactivity will in turn limit learning from errors, since AEs represent opportunities for learning, communication and exchange of experiences between caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tunisia, reporting systems remain uncommon in hospitals and reporting culture is very little developed. This is demonstrated through the patient safety culture surveys carried out in ICUs and where the dimensions related to frequency of events reported and non-punitive response to error had the lowest scores [ 16 , 17 ]. There is no national reporting system, nor a specific regulation relating to the implementation of reporting systems in hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisia, reporting systems remain uncommon in hospitals and reporting culture is very little developed. This is demonstrated through the patient safety culture surveys carried out in ICUs and where the dimensions related to frequency of events reported and non-punitive response to error had the lowest scores [13,14]. There is no national reporting system, nor a speci c regulation relating to the implementation of reporting systems in hospitals.…”
Section: Introductionmentioning
confidence: 99%